2013
DOI: 10.1680/jees.2013.0040
|View full text |Cite
|
Sign up to set email alerts
|

Recent studies in environmental applications of ultrasound

Abstract: As a young, new, and rapidly growing science, the applications of ultrasound in environmental technology hold a promising future. Compared with conventional methods, ultrasonication can bring several benefits such as environmentally friendly (no toxic chemicals are used or produced), low cost, and compact (allowing on-site treatment). Beside an overview on ultrasonic background, this paper summarizes main findings and innovations of recent studies that used ultrasound in environmental analysis, water and sludg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Sonication prevents microbial biofilms (Wang et al 2017 ) and can increase the rate of bacterial cell growth (Pitt and Ross, 2003 ). Ultrasonication is already used in soil and sediment remediation (Radu et al 2020 ) and could serve as an environmentally friendly (no toxic chemicals are used or produced), low cost, and compact (allowing on-site treatment) solution to improve the spreading of inoculated bacteria across the host matrix (Pham et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sonication prevents microbial biofilms (Wang et al 2017 ) and can increase the rate of bacterial cell growth (Pitt and Ross, 2003 ). Ultrasonication is already used in soil and sediment remediation (Radu et al 2020 ) and could serve as an environmentally friendly (no toxic chemicals are used or produced), low cost, and compact (allowing on-site treatment) solution to improve the spreading of inoculated bacteria across the host matrix (Pham et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonic irradiation is a powerful way to degrade a variety of pollutants and toxic chemicals [1][2][3]. Demonstrated examples for ultrasonic removal in aqueous media include fuel oxygenates [4], a variety of chlorinated compounds [5], series of phenols [6,7], arsenic species [8], polycyclicaromatic compounds [9], textile dyes [10,11], and surfactants [12].…”
Section: Examples Of Environmental Applicationmentioning
confidence: 99%
“…Tiehm et al (2001) and Zhang et al (2008a) found that DD COD decreased owing to the increase in frequency (41-1068 kHz and 25-150 kHz, respectively), indicating that mechanical effects, instead of free radicals, are responsible for the biodegradability enhancement. It is therefore important to note that in most works sludge disintegration is the most significant at low frequencies (Pham et al, 2009;Carrère et al, 2010;Pilli et al, 2011). However, the lowest investigated values of frequency in this field have been restricted to around 20-25 kHz.…”
Section: Ultrasonic Frequencymentioning
confidence: 99%